The Implementation of English Learning in New Normal Situation at SDN Percobaan Palangka Raya - Bella Oktariana (Satya Sastraharing : Jurnal Manajemen, 2023)
The research aimed to describe: (1) the implementation of English learning in new normal situation at SDN Percobaan Palangka Raya, (2) the obstacles faced of English learning in new normal situation at SDN Percobaan Palangka Raya, and (3) the efforts to overcome the obstacles faced of English learning in new normal situation at SDN Percobaan Palangka Raya. This research used the descriptive-qualitative method. The subjects were an English teacher and students of class IV-C. Research data was obtained through observation and interviews. Data analysis was analyzed through data reduction, data display, and conclusion drawing. The findings revealed that English learning in a new normal situation at SDN Percobaan Palangka Raya implements face-to-face learning where an English lesson is carried out within an hour. During English learning, students were passive. The English teacher used the lecture, demonstration, question-answer, and assignment methods to convey the material. The obstacles faced during English learning were the different students’ learning motivations and lack of understanding of the learning material. In overcoming the obstacles, an English teacher seeks to manage the classroom atmosphere and guide students who do not understand the material by repeating the learning explanation.